A holistic assessment of the use of teak at a landscape level in Luang Phrabang, Lao PDR - Keonakhone, Thongsavanh (SLU/Dept. of Soil Sciences, 2006)
Teak (Tectonia grandis) plantation establishment in Lao PDR started in 1942, and has strongly increased since 1980. The total area of teak plantations in the Luang Phrabang province is estimated at 5 587 hectares. Pak Ou district is one of the most important areas with teak plantations in the Luang Phrabang province. An attempt was made by the Teak Research Station in Luang Phrabang to test effects of technologies such as thinning and pruning on teak growth during a 2-3-year period during 2002-2004. This thesis work aims at evaluating the effects of these forestry practices from both bio-physical and socio-economic aspects.